Hypocalcaemia after Total Thyroidectomy (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To determine whether postoperative hypocalcemia after total thyroidectomy is more frequent in malignant disease than benign disease.Methods: This is a Cross sectional study. The sample size is 126. All the patients were selected according to the eligibility criteria by purposive sampling. Patients were analyzed for age, gender, thyroid pathology, preoperative serum calcium, postoperative serum calcium.Results: Postoperative hypocalcemia was found in 37 (29.37%) patients. Most patients were female (Male: Female= 1: 4.2). Patients having low preoperative serum calcium had developed more postoperative hypocalcemia (p